Alternate Fuel – A Literature Review - Nakkeeran , S. (International Journal of Psychosocial Rehabilitation, 2019)
This study concern with the use of alternate fuels for automobiles. Since the automobiles are the main source of transportation, its usage increases day by day. Thereby it is necessary to identify a cheaper fuel for it. The currently existing and widely used fuel named gasoline also called as petrol. The cost of this fuel day by day increases and also it will be exhausted in future after some years. The another problem currently using fuels are the exhaust. The exhaust consists of NOx, CO, CO2, SOx, lead and other particulates which lead to air pollution and adverse affect on human beings. So it is important to opt for alternate fuels, which are cheaper and less pollutant to environment.